An Interior Inverse Problem for the Diffusion Operator - A. Dabbaghian; H. Jafari; N. Yosofi (Abstract and Applied Analysis)
An inverse problem for the diffusion operator on a finite interval with discontinuities conditions inside the interval is studied. We have shown that the potential function of the diffusion operator can be established uniquely by a set of values of eigenfunctions at the midpoint of the interval and one spectrum.